Photodynamic therapy intheinactivation of bacteriophages with porphyrin and potentiators in wastewater - Oliveira, Cristiana Paula Martins da Silva (2022)
Pathogenic viruses are frequently introduced into marine and estuarine waters through the discharge of treated and untreated sewage, since current treatments are unable to provide virus-free wastewater (WW) effluents, affecting the receiving waters quality and, consequently, human health. The removal of harmful constituents by the conventional treatments comprises a combination of chemical, physical and biological methods. Usually, WW from urban areas is secondarily, rarely tertiary, treated. Although the secondary effluent contains high concentrations of microorganisms, the effect of water dilution makes it acceptable in terms of quality indicators. In tertiary treatment, chlorination is the most common method used to ensure microbiological safety in tertiarily treated effluents. However, its massive utilization, both in free and combined chlorine forms, may lead to the formation of chemical disinfection by-products though the reaction with organic matter present in the effluents, being those chemicals toxic to aquatic organisms, representing potential health hazards. Unfortunately, these conventional methods are limited and may not be adequate to reach the quality levels specified by the guidelines. Photodynamic therapy (PDT) with porphyrins may be a promising approach for the inactivation of pathogens as they are effective in inactivating microorganisms without the formation of potentially toxic products. Some studies have reported an enhancer effect on antimicrobial photodynamic therapy (aPDT) by the combined used of some photosensitizer (PS) with potassium iodide (KI) and hydrogen peroxide (H2O2). The main objective of this study was to evaluate the aPDT efficacy of a PS based on a low-cost formulation constituted by five cationic porphyrins (Form) and its potentiation effect by KI and H2O2 in the inactivation of a T4-like bacteriophage in WW. The experiments were done in phosphate buffered saline and in filtered and non-filtered contaminated wastewater. The aPDT assays in filtered WW (0.45 μm pore-size) were performed with different concentrations of Form (1.0 to 10 μM). In a second phase was evaluated the effect of KI (100 mM) in the photodynamic action of Form (1.0 to 10 μM). The results of these experiments demonstrated that Form is efficient in filtered WW treatment and that the efficacy of bacteriophage photoinactivation is correlated with the concentration of the used PS. When combined with KI, the Form is clearly less effective to inactivate the bacteriophage. To evaluate if the organic matter present in water influences the efficiency of PS, the WW was filtered using three different pore-sized membranes (0.45, 0.30 and 0.22 μm). The results demonstrated that the increase of organic matter promote a significant decrease in the efficiency of Form. In order to evaluate if the efficiency of aPDT to inactivate bacteriophages is maintained when the treatments are performed in non-filtrated WW, the effect of Form alone (10 μM) and combined with H2O2 (2, 5 and 9%) in non-filtered WW was evaluated. The Form alone proved to be an efficient PS to photoinactivate the bacteriophage in non-filtered WW, but the presence of H2O2 enhanced the photodynamic effect. The FORM can be an effective alternative to control viruses in WW, particularly if combined with H2O2.